Living organizational communication :Consuming dialogism and polyphony as practical wisdom in the production of consciousness - Ahmad, Che Mahzan (Journal of International Social Research, 2009)
The realties we know as organizations come to exist through conversations. For years such conversations are shaped by the mainstream Cartesian worldview and Newtonian mechanics. As cracks on the said worldview and fissures on the above mechanics become bigger and wider, the need to look at other ways of seeing and producing a more ‘living conversations’ are inevitable. We suggest Bakhtin’s polyphony as the new way in the production of such ‘consciousness’ (living conversations) for learning creation in the context of organizational communication realm. Polyphony is basically about the construction of voices of characters with equal rights, and it is done with responsibility overseeing by the Third. In this work we argued that polyphony should be celebrated as the wellspring of learning creation following ‘theory of action’ in the context of the production of consciousness, for addressing the issue of future organizational fitness.